Strategi manajemen sumber daya manusia dalam meningkatkan keterlibatan karyawan pada perusahaan modern - salsabila, aulia (Maliki Interdisciplinary Journal, 2026)
Employee engagement is a crucial factor in improving the performance and competitiveness of modern companies, as emotionally and professionally engaged employees tend to be more productive, loyal, and contribute optimally. This article examines effective human resource management (HRM) strategies for enhancing engagement through a literature review of various journals and academic publications. The study’s findings indicate that several key strategies, such as open leadership and communication, a fair reward and recognition system, career development opportunities, the implementation of work-life balance, and structured talent management, significantly influence employee engagement. These strategies not only improve motivation and job satisfaction but also help companies create a positive work culture, reduce turnover, and enhance organizational performance. This article emphasizes that HRM strategy implementation must be consistent, integrated, and adaptive to the needs of the modern workforce to achieve optimal results.